THE ROLE OF DINING ATMOSPHERE IN SHAPING CONSUMER TRUST AND LOYALTY TO IMPROVE THE COMPETITIVENESS OF LOCAL COFFEE SHOPS - Septiani, Stevia; Slamet, Alim Setiawan; Farhana, Farhana (Jurnal Aplikasi Manajemen, 2020)
The development of lifestyle, information technology, and the industrial revolu- tion 4.0 also play a role in shaping the increasing demand for domestic coffee consumption. At this time, the coffee shop business is growing, starting from the SME scale to the global brand scale. Besides the quality of coffee, several other things can attract consumers to visit a local coffee shop, one of which is the dining atmosphere. To increase the role of local coffee shops, this study aims to analyze consumer profiles, analyze consumer buying behavior, and analyze the effect of dining atmosphere and product quality on customer trust and repurchase intention. Primary data collection was carried out using the convenience and purposive sampling method, with the criteria being respondents who were domiciled in Bogor and had visited six coffee shops studied. The population in this study were all consumers in those coffee shops. The number of samples in this study was 426 respondents, who had met the theoretical requirements of the SEM model. The main data processing method used is Structural Equation Modeling analysis. It is known that there are differences in the SEM model results at local and global coffee shops. In the global coffee shop dining atmosphere and product quality significantly affect customer trust. Whereas at the local coffee shop, only the dining atmosphere affects consumer trust. In the next study, the dining atmosphere model can be sharpening with further testing of demographic factors as the moderating variable.